2000
DOI: 10.1128/iai.68.2.456-462.2000
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for CD4+T Lymphocytes in Host Resistance againstCryptococcus neoformansin the Central Nervous System of Immunized Mice

Abstract: The importance of cell-mediated immunity (CMI) and CD4؉ T lymphocytes in host resistance against Cryptococcus neoformans is well documented and is exemplified by the high susceptibility to progressive infection with this pathogen of AIDS patients with reduced CD4 ؉ T-cell numbers. Although much has been learned about the role of CMI in the clearance of C. neoformans from the lungs and other internal organs, less is known about the protective mechanisms in the brain, the organ most frequently involved with a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 45 publications
(43 reference statements)
4
60
0
Order By: Relevance
“…virulent strain [35]. Moreover, mice vaccinated with either heat-killed Cryptococcus cells or culture filtrate antigens showed significant T-cell-dependent delayed-type hypersensitivity reaction and were better protected against subsequent challenge with a virulent strain [36,37]. Similar to these studies on animal models, elevated IFN-γ levels in the CSF, as well as administration of recombinant IFN-γ were directly correlated with better protective response against cryptococcal infection in humans [38].…”
Section: Discussionsupporting
confidence: 72%
“…virulent strain [35]. Moreover, mice vaccinated with either heat-killed Cryptococcus cells or culture filtrate antigens showed significant T-cell-dependent delayed-type hypersensitivity reaction and were better protected against subsequent challenge with a virulent strain [36,37]. Similar to these studies on animal models, elevated IFN-γ levels in the CSF, as well as administration of recombinant IFN-γ were directly correlated with better protective response against cryptococcal infection in humans [38].…”
Section: Discussionsupporting
confidence: 72%
“…Cytokine and antimicrobial molecules, that include IFN-g, TNF-a, IL-1b, IL-4, IL-6, IL-10, IL-12, IL-23, NO, and macrophage inflammatory protein-1a (MIP-1a) upon exposure to fungal antigens, recruit peripheral CD4 C and CD8 C T cells, peripheral macrophages, and neutrophils that are able to seed into the CNS. 69,70 CD40 and IL-2 enhanced the host cell response to C. neoformans in intracerebrally injected mice by up-regulating CD45, CD11 and MHC II on the surface of microglia as well as infiltration of these cells to the site of injection. 71 Experiments performed with IFN-g knockout mice revealed that this cytokine is essential for both microglial cell activation and the anti-cryptococcal efficacy especially after anti-CD40/IL-2 administration.…”
Section: Opportunistic Fungal Infectionsmentioning
confidence: 99%
“…individuals with AIDS and lymphoid malignancies, and recipients of immunosuppressive therapies) (Levitz, 1991;Mitchell & Perfect, 1995;Shoham & Levitz, 2005;Singh et al, 1997Singh et al, , 2008. Previous studies have shown that protective immunity against this organism is dependent upon the induction of Th1-type cytokine responses (Blasi et al, 1994;Buchanan & Doyle, 2000;Chuck & Sande, 1989;Hill & Harmsen, 1991;Huffnagle et al, 1991;Mody et al, 1990;Shoham & Levitz, 2005;Singh et al, 2008;Wormley et al, 2007;Wozniak et al, 2009). Pulmonary infection in BALB/c mice using a C. neoformans strain engineered to produce murine IFN-c (H99c) results in induction of Th1-type cytokines, IL-17A, and significantly reduced fungal burden.…”
Section: Introductionmentioning
confidence: 99%